Family planning and women's and children's health: Long term consequences of an outreach program in Matlab, Bangladesh - Shareen Joshi; T. Paul Schultz (Institute for the Study of Labor (IZA), 2012)
The paper analyzes the impact of an experimental maternal and child health and family-planning program that was implemented in Matlab, Bangladesh in 1977. Village data from 1974, 1982 and 1996 suggest that program villages experienced extra declines in fertility of about 17%. Household data from 1996 confirm that this decline in surviving fertility persisted for nearly two decades. Women in program villages also experienced other benefits: lower child mortality, improved health status, and greater use of preventive health inputs. Some benefits also diffused beyond the boundaries of the program villages into neighboring comparison villages. These program effects are robust to the inclusion of individual, household, and community characteristics. This paper concludes that the benefits of this reproductive and child health program in rural Bangladesh have many dimensions extending well beyond fertility reduction, which do not appear to dissipate after two decades.
urn:nbn:de:101:1-201301212093
Keywords: O12; J13; I12; J16; 330; fertility; family planning; health and development; program evaluation; Bangladesh; Familienplanung; Wirkungsanalyse; Frauen; Mütter; Kinder; Gesundheit; Bangladesch